SPARQL_edit: Editing RDF Literals in Knowledge Graphs via View-Update Translations - Meckler, Sascha; Harth, Andreas (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2023)
In order to improve the adoption of knowledge graphs (KG) in everyday work, non-technical users must be empowered to not only view but to write data in a KG. Whereas most available software tools focus on displaying information, the presented solution helps business users to execute write operations for correcting wrong values or inserting missing values. SPARQL_edit is a Web application that enables users without any knowledge of SPARQL or RDF to view query results and instantly edit RDF literal values of the knowledge graph. The main concept can be summarized as ‘editable SPARQL result table’. If a user modifies the value of an RDF literal in the view, a generic view-update algorithm translates the change into a SPARQL/Update query that updates the correct RDF triple in the KG. Similar to the view update problem in databases, there are restrictions of the SPARQL language features that can be used for creating a view with unambiguous updates to the graph.
CRIS-Team Scopus Importer:2023-12-01